Pengaruh Dana Desa Terhadap Perkembangan Kemandirian Desa di Kecamatan Gantung - Rifky Nur Alhaqi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
The background in this research is the use of village funds aimed at achieving village independence in 7 villages in the Gantung District which has not been maximized, this can be seen from the progress of the development of village independence as seen from the Village Building Index (Index Desa Membangun) which is still not as expected, where for 4 In the last year, there were 2 villages that still had a developing status. The purpose of this study is to find out how the description of the use of village funds and the development of village independence is and the extent to which the influence of the village fund variable on the variable of village independence development in 7 villages in the Gantung District. The research method used is descriptive and verification research methods. The population in this study amounted to 56 respondents and used a saturated sampling technique. The analysis technique uses Pearson correlation analysis and simple linear regression analysis. The results of this study indicate that village funds have a significant effect on the development of village independence in 7 villages in the Gantung District. The results of the correlation calculation show that there is a strong relationship between village funds and the development of village independence. The results of simple linear regression analysis showed that village funds had an effect of 40.7% on the development of village independence, while the remaining 50.3% was influenced by other factors not examined by researchers